Pharmacokinetics, safety, and efficacy of a single co-administered dose of diethylcarbamazine, albendazole and ivermectin in adults with and without Wuchereria bancrofti infection in Côte d’Ivoire - Edi, Constant; Bjerum, Catherine M.; Ouattara, Allassane F.; Chhonker, Yashpal S.; Penali, Louis K.; Méité, Aboulaye; Koudou, Benjamin G.; Weil, Gary J.; King, Christopher L.; Murry, Daryl J. (PLOS Neglected Tropical Diseases, 2019)
Author summary Lymphatic filariasis is a mosquito-borne infection that causes disability in the form of lymphedema, hydroceles, and elephantiasis. It has been targeted for global elimination based on mass drug administration in the total population at risk including many people uninfected with LF. Recently, a single co-administered dose of IVM + DEC + ALB has been shown to be much more effective than the standard treatment with DEC + ALB for sustained clearance of Mf for 3 years based on studies in Papua New Guinea. This study confirms the efficacy and safety of triple-drug therapy for clearing of Wuchereria bancrofti Mf in an African population. The presence of LF did not affect drug levels and the medicines were well tolerated, with 28% and 25% rate of moderate AEs in infected and uninfected individuals respectively, and no severe or serious AEs, supporting the use of triple-drug therapy for mass drug administration. This study shows for the first time that triple-drug therapy also has a potent macrofilaricidal effect, as determined by the reduction in circulating filarial antigen and inactivation of worm nests one year following treatment.